2007
DOI: 10.3844/ajidsp.2007.240.247
|View full text |Cite
|
Sign up to set email alerts
|

HIV Medication Adherence and Substance Use: The Smartest Women’s Project

Abstract: Antiretroviral (ARV) medication for substance users has been a controversial issue with respect to whether current substance users can successfully maintain their medication regimens. This study compared ARV adherence across current substance users, former substance users and those with no history or current use and the relative impact of a medication adherence intervention on all three groups. Of the 481 predominantly African American and Latina women from Miami, New York and New Jersey enrolled in the SMARTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The program was subsequently adapted to include all women living with HIV and translated linguistically and culturally from English into Spanish and Creole. A healthy lifestyle program targeting multiple health risk behaviors was incorporated, and the program was found to reduce stress/ distress and depression and anxiety, decrease HIV viral load, and enhance coping and self-efficacy, while improving health status and quality of life [15][16][17][18][19][20][21][22]. Between 2007 and 2011, a translation of this evidence-Implications Practice: The Stress Management and Relaxation Training/Expressive-Supportive Therapy Women's Program (SWP) can be implemented in community-based practice, utilizing existing community health center staff with diverse education levels and training backgrounds, and achieves improved health outcomes in women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…The program was subsequently adapted to include all women living with HIV and translated linguistically and culturally from English into Spanish and Creole. A healthy lifestyle program targeting multiple health risk behaviors was incorporated, and the program was found to reduce stress/ distress and depression and anxiety, decrease HIV viral load, and enhance coping and self-efficacy, while improving health status and quality of life [15][16][17][18][19][20][21][22]. Between 2007 and 2011, a translation of this evidence-Implications Practice: The Stress Management and Relaxation Training/Expressive-Supportive Therapy Women's Program (SWP) can be implemented in community-based practice, utilizing existing community health center staff with diverse education levels and training backgrounds, and achieves improved health outcomes in women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use may be associated with decreased adherence to HAART [10][12] and subsequent increased rates of virologic failure and HIV disease progression [13], [14]. However, the association of drug use with reduced adherence is not uniform, as participants in the Smartest Women's project reported relatively high levels of adherence regardless of current, former, and never drug use status [15]. Patient persistence with HAART, reflecting the duration of time on therapy, was decreased among former and current injection drug users in Baltimore, with 78% of individuals having one or more treatment interruptions; persons reporting daily IDU had a higher probability of treatment interruptions [16].…”
Section: Introductionmentioning
confidence: 99%
“…low adherence, treatment failure, and ARV resistance) (4750), this association may be due to broader structural deficits in the healthcare system that result in late diagnosis, delayed ART initiation (5153), and poor retention in HIV care (54, 55). A recent study in Miami found that most substance using women living with HIV were capable of attaining adherence rates of 90% or more and undetectable viral loads (56). To receive adequate HIV care, this high-needs population requires providers with expertise in HIV medicine (5760), a substance use stigma-free setting, good patient-provider relations, and care that is integrated with other services (61).…”
Section: Discussionmentioning
confidence: 99%